Students’ participation in post-16 mathematics: a perspective from Wales - Rosemary Jones (Educational Futures)
This paper considers the results of an investigation into the factors influencing students’ participation in AS-Level (Advanced Subsidiary) post-16 mathematics. National statistics for Wales illustrate that considerably fewer females choose to study mathematics at AS-Level. This is despite a similar proportion of females and males achieving A*-C grades at GCSE (General Certificate of Secondary Education) mathematics. This paper considers evidence from pupils which helps to identify some of the main influences on students’, and in particular girls’, mathematical participation. Supported by considerable statistical data, this paper suggests that anxiety about, confidence in and enjoyment of mathematics are all significant factors on students’ mathematics AS-Level choices, with gender stereotypical career aspirations also being a determining influence on students’ subject preferences.